2007
DOI: 10.1039/b618207k
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular associates of para-aminobenzoic acid with N- and N,O-heterocyclic molecules

Abstract: A series of novel supramolecular multicomponent complexes of para-aminobenzoic acid (PABA) with N-containing cyclic molecules and aza-crown ethers, (H 2 PPz)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
4
12
0
Order By: Relevance
“…We have previously shown that interaction of hexafluorosilicic acid with p-aminobenzoic acid, sulfanilamide and 5-amino-1-benzyl-1,2,3-triazol-4-carbonic acid yielded the corresponding hexafluorosilicates with the aromatic cations formed due to protonation of the terminal amino group [6,12,13]. In a similar way, we expected the formation of the corresponding hexafluorosilicates starting from the sulfa drugs sulfathiazole and sulfalen.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…We have previously shown that interaction of hexafluorosilicic acid with p-aminobenzoic acid, sulfanilamide and 5-amino-1-benzyl-1,2,3-triazol-4-carbonic acid yielded the corresponding hexafluorosilicates with the aromatic cations formed due to protonation of the terminal amino group [6,12,13]. In a similar way, we expected the formation of the corresponding hexafluorosilicates starting from the sulfa drugs sulfathiazole and sulfalen.…”
Section: Resultsmentioning
confidence: 63%
“…The crystal structure is stabilized by the network of hydrogen bonding. All fluorine atoms are involved in the hydrogen-bonding system ( 6 ] 2À anion via the imine NH-site ( Fig. 2(a)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functionalized (oxime, N→O, sulfoxide) pyrimidine derivatives, being coupled with diaza-18-crown-6, revealed different modes of deprotonation (terminal oxime or sulfoxide functionalities or NH of pyrimidine ring) that results in proton-transfer complexes organised in 2D or 3D networks via charge-assisted hydrogen bonds [3]. Anhydrous or hydrated protontransfer complexes were obtained by Aspirin, salicylic, mefenamic or p-aminobenzoic [4] We want to design flexible dynamic frameworks that can create pores to include small guest molecules [1]. These dynamic pores come from a sort of "bistability" of the soft apohost framework, capable to convert from a closed to an open phase in response to guest molecules [2,3].…”
mentioning
confidence: 99%